A critical investigation of leadership in a Technical, Vocational Education and Training college in the Eastern Cape - Chagi, Nonkonzo (Rhodes University, Faculty of Education, Department of Education, 2020)
Far-reaching reforms of the TVET college system "“ including a merger and frequent revisioning of the colleges' role in the educational landscape of South Africa "“ have focused renewed attention on this sector. The fact that the sector has been plagued by poor performance "“ even to the extent that several colleges have been placed under administration "“ suggests problems at the level of leadership. This study sought to explore key role-players' understanding of the leadership and management challenges faced by a TVET college and, by examining responses to these challenges, develop a sense of what leadership means in the sector. The study drew on three leadership theories "“ distributed leadership, transactional leadership as depicted in political models of management, and critical leadership "“ to help make sense of the findings. A qualitative case study design was used to explore key respondents' views and lived experiences. The respondents were the principal, two deputy principals, a council member, three campus managers and a programme head. Interviews, questionnaires and document analysis were the chief data collection tools. The study found that critical leadership was the dominant approach at the college. This was revealed in the college leadership's awareness of broader societal needs and its own role in operating in a socially just manner. College leadership also revealed signs of rejecting the status quo and opposing state control and bureaucracy, in favour of reactionary initiatives. There was limited evidence of distributed and transactional leadership. In fact, 'leadership' as such, seemed not to be part of the college discourse, suggesting that the concept and habit of leadership was not broadly discussed, shared and promoted. This sense was strengthened by the fact that at the time of the study, the college was headed by a charismatic and visionary leader. Indeed, the problem at the college seemed to be the Department of Higher Education and Training, which has failed the college in a number of ways.
Keywords: Technical education -- South Africa; Vocational education -- South Africa; Educational leadership -- South Africa; Postsecondary education -- South Africa -- Administration